Physiological Responses of Elite Karate Athletes During Simulated Competition - Herrera-Valenzuela, T; Orihuela-Diaz, P (STOWARZYSZENIE IDOKAN POLSKA-IDOKAN POLAND ASSOC, 2019)
Background: Physiological measurements during simulated competitions are useful to make training programs more specific to sport-specific demands. Problem and Aim: The objective of the present study was to analyze the physiological response of kumite karate athletes during a simulated competition. Methods: Ten athletes from Chile s national karate team (5 males, age: 24.2 +/- 1.8 years, height: 1.67 +/- 0.07 m, body mass: 77.8 +/- 16.7 kg, and 5 females, age: 23.2 +/- 4.1 years, height 1.61 +/- 0.04 m, body mass: 62.2 +/- 3.7 kg) participated in a simulated competition composed of 4 matches for each athlete. We measured the following variables: blood lactate concentration, heart rate, rating of perceived exertion, respiratory rate, and body temperature. Results: An effect of time on body temperature was for found in males and females, heart rate mean in males (P = 0.009), and 1-minute heart rate recovery in females (P = 0.044). Conclusions: The simulated karate competition under the new Olympic weight categories presented elevated cardiovascular and metabolic responses, which increased in intensity as the fighting progressed.